A Learning Community in the Primary Classroom. - Brophy, Jere (Taylor & Francis, 2010)
Offering a description and analysis of exemplary teaching in the primary grades, this title examines how a teacher can establish a classroom collaborative learning community. It also helps to plan curriculum and instruction that features ideas and applications to life outside of school, and motivate students to learn with a sense of purpose.